Review of the book by A.A. Chibilev “Pictures of Nature of Steppe Eurasia”: Volume 1: From the Foothills of the Alps to the Southern Urals. Moscow & Orenburg: Steppe Institute of the Ural Branch of the Russian Academy of Sciences; Russian Geographical Society, 2018. 172 p.; Volume 2: From the Urals to the Irtysh. Moscow & Orenburg: Steppe Institute of the Ural Branch of the Russian Academy of Sciences; Russian Geographical Society, 2019. 184 p. - G. S. Rozenberg (Юг России: экология, развитие)
This review was written during self‐isolation and remote access to work in connection with the COVID‐19 coronavirus pandemic.